The Impact of Family Psychoeducation on Medication Adherence in Schizophrenia Clients for Preventing Rehospitalization - Aisah Mamang; Neng Esti Winahyu; Okti Hanalutfi Kahiriyah; Dede Anwar Musadad; Rustika Rustika (Indonesian Journal of Global Health Research, 2025)
Schizophrenia is a serious mental illness that can significantly impact the quality of life. Families play a crucial role as primary caregivers, providing both physical and mental support to individuals with schizophrenia. Family psychoeducation therapy is a structured intervention designed to address relapse-related challenges in schizophrenia clients. The purpose of this study was to examine the impact of family psychoeducation interventions on medication adherence in schizophrenia clients. This study used a quasi-experimental design with 62 families divided randomly into intervention and control groups (31 each). Families with a member diagnosed with schizophrenia and willing to participate were included. The intervention group received four weekly psychoeducation sessions, while the control group received standard care. Medication adherence was measured using a validated scale. Data were analyzed with the Mann-Whitney U test (p < 0.05) to assess the intervention’s impact. The study found no significant effect of psychoeducation on medication adherence based on age (p = 0.968), gender (p = 0.172), and education level (p = 0.148). However, there was a significant effect of psychoeducation on medication adherence related to employment (p = 0.023), knowledge (p = 0.023), attitudes (p = 0.001), and overall adherence (p = 0.001). The family psychoeducation intervention program showed significant benefits, including improved medication adherence, better family perceptions of medication, enhanced understanding of schizophrenia, and reduced relapse rates and hospital readmissions.